Presencia de un polimorfismo de la CSP-12 relacionado con susceptibilidad a sepsis grave en una muestra de tres poblaciones colombianas (2010)
ABSTRACT: Sepsis, a syndrome of systemic response to infection is a major public health problem, because it is associated with high morbidity and mortality. Among the genes shown to be associated with this syndrome, there is one which encodes for caspase-12 (csp-12). Within this gene, the single nucleotide polymorphism 125T>C located in exon 4, which predicts a long form of the protein, has been associated with severe sepsis and increased related mortality. On the other hand, higher frequency of allele L has been reported in African American populations. The present study evaluated the csp-12 polymorphism 125T>C in 128 individuals: 81 patients with sepsis, 23 healthy African Colombian subjects and 24 healthy individuals from Medellin-Colombia. We found 121 individuals homozygous S/S (csp-12 short) in these three populations and 7 heterozygotes S/L, discriminated as follows: 3 septic patients, 3 African Colombians and 1 healthy subject from Medellin. This preliminary data suggest that the csp-12L allele is present in the Colombian population, both in African Colombians and Mestizo individuals (either septic patients or healthy individuals).Therefore, more comprehensive studies should be performed to better understand the genetic basis of the immune response of patients with sepsis in order to design more rational and personalized therapies to prevent this syndrome.